Effects and mechanisms of the myocardial microenvironment on cardiomyocyte proliferation and regeneration - Zheng, Kexiao; Hao, Yanglin; Xia, Chenkun; Cheng, Shaoxian; Yu, Jizhang; Chen, Zhang; Li, Yuan; Niu, Yuqing; Ran, Shuan; Wang, Song; Ye, Weicong; Luo, Zilong; et al. (Frontiers in Cell and Developmental Biology, 2024)
The adult mammalian cardiomyocyte has a limited capacity for self-renewal, which leads to the irreversible heart dysfunction and poses a significant threat to myocardial infarction patients. In the past decades, research efforts have been predominantly concentrated on the cardiomyocyte proliferation and heart regeneration. However, the heart is a complex organ that comprises not only cardiomyocytes but also numerous noncardiomyocyte cells, all playing integral roles in maintaining cardiac function. In addition, cardiomyocytes are exposed to a dynamically changing physical environment that includes oxygen saturation and mechanical forces. Recently, a growing number of studies on myocardial microenvironment in cardiomyocyte proliferation and heart regeneration is ongoing. In this review, we provide an overview of recent advances in myocardial microenvironment, which plays an important role in cardiomyocyte proliferation and heart regeneration.